Investigating the biological roles of the HSPRO genes in Arabidopsis thaliana - Guzha, Delroy Tapiwa (Department of Molecular and Cell Biology, 2015)
As a consequence of an immobile lifestyle, plants have had to evolve appropriate perception mechanisms and responses to diverse environmental stresses. Stress can be the result of both biotic and abiotic agents and the ORTHOLOG OF SUGAR BEET HS1 PRO-1 (HSPRO 1) and HSPRO2 genes were previously shown to be induced in response to several stresses including infection with Pseudomonas syringae and drought stress in Arabidopsis thaliana. The aim of this study was to characterise the biological role(s) played by these proteins in Arabidopsis. Several bioinformatics approaches provided evidence that supported function of both genes in response to both biotic and abiotic stresses and identified potential regulatory elements that may drive HSPRO gene expression during stress responses. Accordingly, analysis of null hspro mutants revealed antagonistic functions of the two proteins in PAMP-triggered immunity to P. syringae infections of shoot tissues and osmotic stress tolerance in plant roots. HSPRO proteins have been shown to interact with a central integrator of stress and energy signalling, SUCROSE NON-FERMENTING-1-RELATED KINASE1 (SnRK1) and microarray analysis of the null mutants suggested potential roles in carbohydrate signalling. An array of energy responsive genes including a subset of SnRK1 targets were misregulated in hspro mutants under standard growth conditions supporting involvement of HSPRO in energy signalling. Mutant phenotype and gene expression analysis revealed that HSPRO2 may be of importance in energy perception as hspro2 seeds were hypersensitive to exogenous glucose during germination, and that perception and/or signalling of low energy status may require HSPRO2. Although HSPRO2 expression may be driven via perception of environmental stress cues, promoter-luciferase assays revealed a diurnal expression pattern of the gene that was driven by the circadian clock. However, phenotypic analysis did not reveal a requirement of HSPRO2 for normal clock modulation. Since stress perception typically causes fluctuations in energy levels, it is proposed that HSPRO genes are important for the integration of energy and stress signalling in an effort to maintain a homeostatic balance between coping with environmental stress and normal growth and development.